The Impact of Islamic Religious Education on Students’ Ramadan Fasting Practices: A Quantitative Study - Zubairi, Zubairi; Abnisa, Almaydza Pratama (Didaktika Religia, 2023)
The article examines the relationship between learning Islamic Religious Education (PAI) (variable X) and students' practice of Ramadan fasting (variable Y). With a population of 216 students and a 10% margin of error using the Slovin formula, a sample size of 68 students was determined. Using a descriptive method and analysis with the product moment formula, the results showed that PAI learning has a significant positive effect on the practice of Ramadan fasting, with a count value of 148.843 greater than the table value of 1.997, a very strong correlation coefficient of 0.99, and an influence level of 1%, while the remaining 99% is influenced by other factors. The results suggest that students who receive high-quality PAI teaching tend to be more active and consistent in their fasting practices. Factors such as understanding of religious concepts, moral values, and social support from PAI teachers play a crucial role. The practical implications suggest the need to improve the quality of PAI learning in order to better support students in their Ramadan fasting practices.